Percepção de profissionais de saúde de três municípios sobre o atendimento à hanseníase - Donda, Priscila (2016)
Leprosy patients should be attended to in primary care, the main entrypoint for healthcare, since the diagnosis is essentially clinical and epidemiological. Continuous education in healthcare has a great potential to change the routine of services, due to the closeness of practice in the life of professionals. OBJECTIVE: to understand the leprosy program carried out by health professionals at Primary Care in three municipalities in the northwest of the State of São Paulo. METHODS: this is a qualitative study of 57 professionals involved with leprosy indicated by the managers of healthcare facilities in three towns in the northwestern region of São Paulo State. Those who did not agree to participate in the study were excluded. Individuals answered a questionnaire to assess their knowledge about leprosy. The results of these questionnaires identified gaps in knowledge that were used in the planning of discussion circles. The discussion circles were based on the assumptions of education (conscientizing/problematizing) of Paulo Freire. Using Bardin's content analysis, three categories with two units of meaning (UM) in each were constructed. RESULTS: Category 1: Current context of leprosy. The population and health professionals present fear, preconception and difficulty to understand the concepts of leprosy.UM 1a: Sociocultural aspects. Feelings linked to ignorance about leprosy and, by the belief that it is a "danger" to others. Lack of knowledge of the population, coupled with other sociocultural and economic aspects, make people vulnerable and propitious to spread the disease. UM 1b: The work of the Health team: knowledge and customer service, knowledge among professionals results in quality care and reflects in a reduction of the bacillary load, increases the early diagnosis rate, and decreases the consequences of the disease. Category 2: Health management and control of leprosy.UM 2a: The leprosy care structure included knowledge of the epidemiological situation, access to services, transportation, admission to the facility, reference and counter-reference systems, treatment flow, communication and health records. UM 2b: Human resource management was related to excess of work, employee turnover, teamwork, ties and layoffs. UM 2b: Human resource management is the training and qualification of professionals. Category 3: Desired and necessary change. UM 3a: Reviewing the work context: reflections on the treatment of leprosy. In the discussions, the creation of a fertile environment for joint reflections allowed visualization of other conducts, which in this case, intended to meet the real needs of the patient. UM 3b: Modifying a practice: a way to meet user needs. This generated ideas on the design of flow charts and protocols for treatment, on education and the addition of new professionals. FINAL CONSIDERATIONS: This study clearly shows that "understanding the world" and "sharing with others" transformed the people who participated in the discussion circles. The previous solitary vision allowed for emancipation, the empowerment of those involved and a feeling of responsibility to gain knowledge. It revealed the difficulties in treating leprosy patients and possible suggestions to transform to the reality of each municipal, notable evolution from the discovery and understanding the reality.